ANALISIS HUBUNGAN ANTARA KONSTANTA PEGAS DAN DEFLEKSI STATIS DENGAN PEMBEBANAN BERBEDA TANPA PEREDAM - Jumiadi; Dewi Izzatus Tsamroh; Ike Widyastuti; Arif Budiono (RING ME, 2023)
One of the most frequently encountered motions in nature is oscillatory motion (vibration). A particle oscillates when it moves periodically about an equilibrium position. A load attached to a spring that is stretched once is released, then it begins to oscillate. Basically, vibration is a technical system that contains mass and elasticity that is able to move relatively or can be said to be a movement that repeats itself at certain time intervals. Increasing technological developments show that the tools that have to do with vibrations are very diverse. One of them is the vibration that utilizes the Simple Vibration Apparatus. In the free vibration frequency experiment, from the test results without a damper with a mass of 0.47kN/m; 1.22kN/m and 3.3kN/m it can be seen that there is a big difference between the theoretical frequency value and the actual frequency value. The results of the theoretical deflection from experiments 1 - 5 have increased constantly. The greater the loading, the greater the deflection.